The institute of the grape. Brief historical review (Gestión y Gerencia, 2022)
This review describes the process of creation and consolidation of the Instituto de la Uva, of Universidad Centroccidental Lisandro Alvarado (UCLA) which includes historical passages since its foundation and brief comments on its research, teaching, extension and production activities. Mention is made of its academic staff and experimental fields. The review ends by pointing out the current situation of the Institute, in which much of its surface, infrastructure and equipment has been invaded and looted by unscrupulous people.
Keywords: Instituto de la Uva; grape; vineyards; viticulture; wine; enology